Umrah Service Strategy Based on Experiential Marketing (Case Study of Amana Tour and Travel, Yogyakarta) - M. Zikrullah Fifnanda; Aris Risdiana; Reza Bakhtiar Ramadhan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The purpose of this research is to know the experiential marketing strategy for the development of experienceand to maintain the customer experience in Amana Tour & Travel Yogyakarta. Marketing a productessentially needs to know the sustainability and durability of the products on the market. Considering theubiquitous umroh service providers, strategies are needed to win the competition in a healthy manner. Inaddition, this strategy is used to be able to present a good experience in the customer's mind and is certainlyable to maintain and enhance the experience. After conducting research, it can be seen that the experientialmarketing strategy at Amana Tour & Travel Yogyakarta in general is to change the negative stigma of theUmrah travel agency that currently exists. This is done by Amana Tour & Travel through 3 ways whichare building good and strong brand architecture, presenting and maintaining a good customer experience,and bridging the presence of customer experience using experience providers. For building customerexperience and maintaining strategies, Amana Tour & Travel applies the principle of a flowing system.This principle emphasizes the ease and comfort of customers in a variety of services both when registeringthemselves, when on pilgrimage, and upon arrival in Indonesia. Amana Tour & Travel also implements afamilial system with the congregation by communicating as well as possible, one of which is by holdingreligious studies that also involve the wider community.